Study of prescription pattern in emergency psychiatry in a tertiary care academic hospital of a developing country: a retrospective study - Nath, Kamal; Naskar, Subrata; Victor, Robin; Saxena, Kaveri (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Prescription pattern study of psychotropic drugs gives a picture of drug preference and rationality of drug use by psychiatrists of a region. The aim of the study was to explore the prescription pattern of psychotropic drugs in emergency settings in a tertiary care centre in a developing country. Methods: A total of 1153 prescriptions were analysed in the study. Data was extracted retrospectively from the psychiatry department emergency register of a tertiary care hospital, in north-eastern India for a period of one year. Results: The most commonly used psychotropic drug in emergency setting was found to be anxiolytic and hypnotics (60.96%) in which clonazepam (48.6%) was commonest. Antipsychotics followed next (14.5%), out of which 69.6% were atypical antipsychotics with olanzapine being the commonest. Conclusions: Use of parenteral typical antipsychotic was found to be much higher, than expected. For the benefit of the mass, supply of cost effective parenteral atypical antipsychotics is the need of the hour in this part of the world.